New 1,2,4-oxadiazole derivatives with positive mGlu4 receptor modulation activity and antipsychotic-like properties - Anna Stankiewicz; Katarzyna Kaczorowska; Ryszard Bugno; Aneta Kozioł; Maria H. Paluchowska; Grzegorz Burnat; Barbara Chruścicka; Paulina Chorobik; Piotr Brański; Joanna M. Wierońska; Beata Duszyńska; Andrzej Pilc; et al. (Taylor & Francis Group, 2022)
Considering the allosteric regulation of mGlu receptors for potential therapeutic applications, we developed a group of 1,2,4-oxadiazole derivatives that displayed mGlu4 receptor positive allosteric modulatory activity (EC50 = 282-656 nM). Selectivity screening revealed that they were devoid of activity at mGlu1, mGlu2 and mGlu5 receptors, but modulated mGlu7 and mGlu8 receptors, thus were classified as group III-preferring mGlu receptor agents. None of the compounds was active towards hERG channels or in the mini-AMES test. The most potent in vitro mGlu4 PAM derivative 52 (N-(3-chloro-4-(5-(2-chlorophenyl)-1,2,4-oxadiazol-3-yl)phenyl)picolinamide) was readily absorbed after i.p. administration (male Albino Swiss mice) and reached a maximum brain concentration of 949.76 ng/mL. Five modulators (34, 37, 52, 60 and 62) demonstrated significant anxiolytic- and antipsychotic-like properties in the SIH and DOI-induced head twitch test, respectively. Promising data were obtained, especially for N-(4-(5-(2-chlorophenyl)-1,2,4-oxadiazol-3-yl)-3-methylphenyl)picolinamide (62), whose effects in the DOI-induced head twitch test were comparable to those of clozapine and better than those reported for the selective mGlu4 PAM ADX88178.